A NK Cell Odyssey: From Bench to Therapeutics Against Hematological Malignancies - Ramos-Mejia, Veronica; Arellano-Galindo, Jose; Mejía-Arangure, Juan Manuel; Cruz-Munoz, Mario Ernesto (Frontiers in Immunology, 2022)
In 1975 two independent groups noticed the presence of immune cells with a unique ability to recognize and eliminate transformed hematopoietic cells without any prior sensitization or expansion of specific clones. Since then, NK cells have been the axis of thousands of studies that have resulted until June 2021, in at least more than 70 000 publications indexed in PubMed. As result of all these researches, that have included approaches in vitro, in vivo, and in natura, it has been possible to appreciate the role played by the NK cells, not only as effectors against specific pathogens, but also as regulators of the immune response. Recent advances have revealed previous unidentified attributes of NK cells including the ability to adapt to new conditions under the context of chronic infections, or their ability to develop some memory-like characteristics. In this review, we will discuss significant findings that have rule our understanding of the NK cell biology, the developing of these findings into new concepts in immunology, and how these conceptual platforms are being used in the design of strategies for cancer immunotherapy.